Bank reputation in the private debt market - McCahery, Joseph; Schwienbacher, Armin (Journal of Corporate Finance, 2010)
We examine the impact of lead arrangers' reputation on the design of loan contracts such as spread and fees charged. Controlling for the non-randomness of the lender–borrower match (self-selection bias), we find that the reputation of top tier arrangers leads to higher spreads, and that top tier arrangers retain larger fractions of their loans in their syndicates. These larger spreads are especially pronounced for borrowers without credit rating that have the most to gain from the certification assumed by virtue of a loan contract with a top tier arranger. This certification channel differs from the one found in public markets, where certification leads to a reduced spread offered to the best clients. These differences between public and private markets can be explained by differences in the way they operate and are structured. Interestingly, the effect is strongest for transactions done after the changes in the banking regulations (including the Riegle-Neal Interstate Banking and Branching Efficiency Act of 1994) that led to significant consolidations in the banking industry, including among the largest commercial banks.